Ácido úrico sérico na doença renal crônica: uma experiência na atenção primária à saúde e uma revisão sistemática e metanálise - Gonçalves, Danilo Lemes Naves (2020)
The current demographic and epidemiological transition has increased the burden of chronic non-communicable diseases (CNCD) such as hypertension (HA) and diabetes (DM), that are the main causes of chronic kidney disease (CKD). The increased serum uric acid levels (SUA) also has been related to the development and progression of CKD. Although the CKD is a sensitive condition to Primary Health Care (PHC), the control, the early detection and the timely referral to other points in the Healthcare Network are still a challenge to the PHC professionals. In this context, this study aimed to estimate the prevalence of CKD and its association with SUA in hypertensive and/or diabetic patients registered in PHC. In addition, a systematic review and meta-analysis was conducted in order to elucidate the relationship between SUA and CKD in the scientific literature. The cross-sectional study evaluated demographic, clinical, behavioral and biochemical variables in the medical record of registered users of a Family Health Strategy in Araguari (MG) between 2019 and 2020. The diagnosis of CKD was based on the measurement of serum creatinine and calculation of the glomerular filtration rate using the CKD-EPI formula and was confirmed in 90 days. The prevalence of CKD in the sample was 17% (95% CI = 12.1–23.3). The increase of 1 mg/dL in the SUA increased the chance of the hypertensive and/or diabetic population to present CKD by 1.6 times, after adjustment for age, sex, HA, DM, cardiovascular diseases, dyslipidemia, smoking, alcoholism and medications. The systematic review showed that high levels of SUA are a risk factor for the incidence of CKD (1.23 [95% CI = 1.14-1.31]). However, it is not associated with the progression of the disease (HR = 1.02 [95% CI = 0.97-1.08]). Thus, we conclude that the high levels of SUA can provide with the incidence of CKD.